Evaluasi Optimalisasi Alat Gali Muat dengan Metoda Overall Equipment Effectiveness (OEE) untuk Memenuhi Target Produksi Batubara Bulan Maret 2018 di Pit 1 Utara Bangko Barat PT.Bukit Asam Tbk, Tanjung Enim Sumatera Selatan - Yugo Agustino; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. Based on coal production data in North Pit 1, West Banko Mine PT. Bukit Asam, Tbk in March-May 2018, coal production does not reach the target. This is due to the low productivity of the excavator. To find out the improvement potential of a production process and the effectiveness of using an equipment, it is necessary to do an analysis using the Overall Equipment Effectiveness (OEE) method. OEE is known as one of the applications of total productive maintenance programs that have the ability to clearly identify the root of the problem and its causal factors so as to make the improvement effort more focused. After the root cause of the problem is known, it is used multiple linear regression statistical analysis and simple linear regression to determine the relationship and the maximum limits of the obstacles so that production can be achieved. After analysis and improvement with these methods obtained the production of backhoe komatsu PC 400LC, volvo EC 480DL, volvo EC 330BLC exceeded the planned target. However, the OEE value of each excavator still <85% has not reached world-class OEE value> 85%, it can be concluded that the condition of the equipment is not good. It is better to do repairs to standby time and tool breakdown. Keywords: Production, Overall Equipment Effectiveness (OEE), Linear Regression Statistical Analysis, Back Hoe, Standby Time